DECISION OF THE OPEN ASSIGNMENT PROBLEM BY STANDARD SIMPLEX METHOD - V. S. Mukha (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The algorithm for the automatic decision of open assignment problem of any size by standard simplex method is designed.